Implementation of Islamic Management based on Maqasid Sharia in Information Services Company (Case Study: Islamic Analytix Singapore) - Wily Mohammad; Dian Tiara Nurhasanah (Journal of Social Science, 2021)
Management is the art of regulating the process of utilizing human resources and other sources effectively and efficiently to achieve certain goals. Management has been used by many companies in this world, also has been influenced by social values including religion. Muslims who always adhere to Islamic law as a way of life properly will receive benefits in the form of Maqasid Sharia based on the level of Maslahah given by Allah. Humans, as the manager for themselves, for their family, or for their organization also really need to protect things in the concept of Maqasid Sharia and determine the level of protection using the concept of Maslahah. This can also be applied to companies, especially if its people are muslim, to make the company, management, and the people therein happy, live long, and blessed by Allah. Islamic Analytix is an Information Services company based in Singapore. This company provides Market Research, Market Analytics, and Market Intelligence through the platform. The staff, managers, and directors are mostly Muslim. The result of this research shows that Islamic Analytix Singapore is implementing Islamic management based on Maqasid Sharia. It can be seen from the good religious attainment (ad-Din), good quality of the life (an-Nafs), good quality of science or intellect (al-Aql), good quality of offspring (an-Nasl), and good quantity of wealth (al-Maal). These results also according to the maslahah concept such as primary needs (dharuriyyat), secondary needs (hajjiyyah), and tertiary needs (tahsiniyyah).